"Not tonight zebrafish": the effects of Ruta graveolens on reproduction. (1st January 2018) - Forsatkar, Mohammad Navid; HedayatiRad, Maryam; Luchiari, Ana Carolina
Abstract: Context: There is growing interest in the pharmacological evaluation of Rue due to its potential to treat a variety of clinical diseases. The plant seems to present potent endocrine disrupting effects, and its excretion and disposal are not a concern. Objective: The effects of Ruta graveolens L. (Rutaceae) ethanol extract (RE) on reproductive behaviour, fertility, and steroid and thyroid hormone levels in zebrafish were investigated. Material and methods: We exposed subjects to varying concentrations of RE, and one-tenth the LC50 concentration (2.37 ppm) was established as the sublethal dose. After 2 weeks exposure, reproductive behaviour, cumulative number of eggs laid, percentage of fertilized eggs, and whole body steroid and thyroid hormones were measured. Results: Reproductive association behaviour did not differ between control and RE-exposed animals, but spawning attempts were reduced in RE exposed animals. Cumulative egg production between days 9 to 14, RE exposed fish laid 672 eggs while control fish laid 1242 eggs. Also, percentage of fertilized eggs was higher for the control than for the RE exposed fish. Estradiol-17β (E2) levels were reduced in females exposed to RE and testosterone (T) was statistically lower in both males and females treated with RE. Furthermore, thyroid hormones (T3 and T4) declined in fish treated with RE. Conclusion: RE has endocrine disrupting potential in fish, which has important implications for studying the effects of unintentional pharmaceutical exposure. Moreover, the results demonstrate that drug exposure may affect more than just the overall level of behaviour, emphasizing the relevance of examining the effects of individual exposure. We reinforce the use of zebrafish as a model organism in physiology and behaviour, and raise concerns about the toxic effects of RE in non-target organisms such as aquatic vertebrates, which may ultimately affect human health.